Procalcitonin vs. the combination of micro-erythrocyte sedimentation rate and C-reactive protein for diagnosing neonatal bacterial sepsis - Afifa Ramadanti; Renya Hiasinta; Herman Bermawi; Erial Bahar (Indonesian Pediatric Society, 2017)
Background Given the high rates of mortality and morbidity in neonatal sepsis, rapid, easy-to-use, and inexpensive biomarkers with high sensitivity and specificity are needed to diagnose neonatal sepsis. Procalcitonin is often used as a predictor in identifying neonatal sepsis, but C-reactive protein (CRP) and micro-erythrocte sedimentation rate (m-ESR) may also be valid biomarkers of neonatal sepsis.Objective To compare the accuracy of procalcitonin to the combination of CRP and m-ESR, as well as to find cut-off points for the three tests, in diagnosing bacterial neonatal sepsis.Methods Subjects were neonates hospitalized from July to October 2016 in Mohammad Hoesin Hospital, Palembang with sepsis at clinical presentation and healthy neonates with sepsis risk factors. All subjects underwent complete blood counts, CRP, m-ESR, blood cultures, and Â procalcitonin examinations.Results Ninety-four infants were included, of whom 26 had proven sepsis. The combined values of m-ESR and CRP had 85% sensitivity, 59% specificity, and 66% accuracy. A procalcitonin (PCT) cut-off point of 9.7ng/mL showed 100% sensitivity, 96% specificity, and 97% accuracy level, which were significantly higher than the combined values of m-ESR and CRP.Conclusion The combined values of m-ESR (13 mm/hour) - CRP (17 mg/dL) and procalcitonin alone (2ng/mL) are both valid for the diagnosis of bacterial neonatal sepsis, but the accuracy of procalcitonin at 9.7ng/mL is significantly greater.Â